Primary muscle hypertrophy of the colon in a cat: a rare presentation - Silva, Juneo F.; Paiva, Bruno H. A.; Ocarino, Natália M.; Serakides, Rogéria (Brazilian Journal of Veterinary Pathology, 2015)
In animals and humans, intestinal muscular hypertrophy has only been observed in the small intestine, and this appears to be the first report of the disease affecting the large intestine. A rare case of primary muscle hypertrophy of the colon was found during the necropsy of a male, 3-year-old, mixed breed cat that died due to poisoning by carbamate. The necropsy revealed that the entire colon had marked circumferential thickening with narrowing of the lumen. Microscopically, diffuse intense smooth muscle hypertrophy was observed, especially of the inner circular muscle layer and muscularis mucosa. Those finds were associated with moderate multifocal to coalescing lymphocytic inflammatory infiltrate. Smooth muscle fibers of the large and small intestine showed no CDC47 expression and the percentage of nuclei in the muscle layers was similar between the colon and the duodenum. Based on macroscopic, microscopic and immunohistochemical findings, the diagnosis of diffuse primary muscle hypertrophy of the colon was confirmed.